2020
DOI: 10.3389/fmats.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Flake-Flower NiO and Its Gas Sensing Performance to CO

Abstract: In this work, flake-flower NiO was successfully prepared via a facile hydrothermal method. The microstructure of the synthesized sample was characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). We find that the hierarchical flake-flower structure was assembled by numerous nanosheets with different size and shape. The fabricated sensor based on the obtained microstructure exhibited excellent gas sensing performance including high respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In our study, it is assumed the concentration of dissolved oxygen (DO) remains constant during the photocatalytic reaction. Pan et al (Li et al 2019) formed by the reaction of the adsorbed oxygen molecules with nickel ions (Norton et al 1977, Qian et al 2020.…”
Section: The Reactions Of the Charge Carriers (The Trapping Process)mentioning
confidence: 99%
“…In our study, it is assumed the concentration of dissolved oxygen (DO) remains constant during the photocatalytic reaction. Pan et al (Li et al 2019) formed by the reaction of the adsorbed oxygen molecules with nickel ions (Norton et al 1977, Qian et al 2020.…”
Section: The Reactions Of the Charge Carriers (The Trapping Process)mentioning
confidence: 99%
“…In particular, a high interest in the preparation of transition metal–metal oxide heterojunction 1D and 2D nanomaterials such as nickel oxide/cobalt oxide (NiO/Co 3 O 4 ), nickel/nickel oxide (Ni/NiO), nickel hydroxide/cobalt oxide (Ni(OH) 2 /Co 3 O 4 ), and α-Ni(OH) 2 has been seen for their applications in supercapacitors, 8 , 9 solar cells, 10 ferro-fluids, catalysis, 11 magnetic materials, 12 gas sensors, 13 , 14 and as efficient anodes in lithium batteries. 15 It is well known that CoO occurs in 6 different oxidation states, such as Co, CoO 2 , Co 2 O 3 , CoO(OH), CoO, and Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…They can also provide surfacedependent electrochemical performance for next-generation batteries and supercapacitor applications. 6,7 In particular, a high interest in the preparation of transition metal−metal oxide heterojunction 1D and 2D nanomaterials such as nickel oxide/cobalt oxide (NiO/Co 3 O 4 ), nickel/nickel oxide (Ni/NiO), nickel hydroxide/cobalt oxide (Ni(OH) 2 / Co 3 O 4 ), and α-Ni(OH) 2 has been seen for their applications in supercapacitors, 8,9 solar cells, 10 ferro-fluids, catalysis, 11 magnetic materials, 12 gas sensors, 13,14 and as efficient anodes in lithium batteries. 15 It is well known that CoO occurs in 6 16,17 Nickel hydroxide Ni(OH) 2 has received great attention due to its high theoretical capacitance for supercapacitor applications and high performance in battery applications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that O2 molecules are adsorbed on the surface of ZnO in both physisorption and chemisorption forms. When the Ni-doped ZnO is exposed to oxygen, the reactive-centers of the Ni-O2 are formed by the reaction of the adsorbed oxygen molecules with nickel ions(Norton et al 1977, Qian et al 2020.In our provided mechanism, the photogenerated electrons are trapped by Ti 4+ , Fe 3+ , Zn 2+ , and Ni 2+ ions in the reactive-centers of Ti 4+ − O 2 (ads), Fe 3+ − O 2 (ads), Zn 2+ − O 2 (ads), Ni 2+ − O 2 (ads), and RGO − O 2 (ads). Besides, silver is considered as a reactive-center, which can accept and transfer the CB electrons of the semiconductor.…”
mentioning
confidence: 99%